WORK FROM HOME AS A STRATEGIC MANAGEMENT TOOL: ORGANIZATIONAL AGILITY IN MALAYSIA’S PUBLIC SECTOR - MARHANI MOHAMED ANUAR; SARINAH SABAR; AINUN NADZIRAH MAHMOOD; IRWAN IBRAHIM (Quantum Journal of Social Sciences and Humanities, 2026)
The implementation of Work From Home (WFH) within the Malaysian public sector has evolved from a temporary operational response into a strategic organizational management approach aimed at improving institutional adaptability and operational continuity. This study examines the influence of strategic leadership, digital readiness, and organizational communication on organizational agility and organizational performance during WFH implementation. Drawing upon Dynamic Capability Theory and the Resource Based View, the study positions organizational agility as a strategic capability that strengthens institutional responsiveness under uncertain working environments. A quantitative cross sectional research design was employed involving 372 government servants from selected federal and state agencies in Malaysia. Data were analysed using Structural Equation Modeling (SEM). The findings revealed that strategic leadership, digital readiness, and organizational communication significantly influence organizational agility. Organizational agility was also found to significantly improve organizational performance and mediate the relationships between the independent variables and organizational performance. The study contributes to strategic management literature by extending the understanding of WFH within public sector organizational transformation and adaptive governance contexts.